Densification of ceria-based barrier layer for solid oxide cells at lower sintering temperatures: A review - Shiyi Wu; Wenyi Yan; Na Ni; Lei Zhu; Zhen Huang (Journal of Advanced Ceramics)
Solid oxide cells (SOCs), including solid oxide fuel cells (SOFCs) and solid oxide electrolysis cells (SOECs), hold great potential for commercial viability because of their high heat utilization, reduced carbon emissions, high efficiency, and fuel flexibility. A key component in enhancing cell performance and extending lifetime is the thin and dense ceria-based barrier layer at the electrolyte and air electrode interface to avoid cell degradation during manufacturing. The barrier layer needs to be densified at low temperatures (ideally less than 1000 °C), which remains a significant challenge. This review focuses on a typical low-cost ceramic powder-based route for the preparation of a barrier layer and explores various approaches to achieve low-temperature densification. It covers techniques such as synthesizing finer powders, optimizing deposition methods for the green-body layer, using sintering aids, and employing post-sintering processes to increase density. Recent advancements in these areas are highlighted to provide insights into future development directions. Finally, the review discusses new opportunities and emerging techniques that could further improve the barrier layer performance.